Teacher Digital Competence Analysis in Block Programming Applied to Educational Robotics - Sánchez-Rivas, Enrique; Ruiz-Roso Vázquez, Coral; Ruiz-Palmero, Julio (Sustainability, 2024)
This research aims to analyze digital teaching competence in the field of block programming applied to educational robotics among active primary education teachers. The research methodology employed is defined as descriptive and exploratory. We gathered quantitative data through a structured questionnaire, reflecting the level of digital competence of the participating teachers. The results obtained from this study reveal significant deficiencies in the development of teaching digital competence, especially in the areas of robotics and educational programming. Importantly, the teachers in the sample exhibit a high level of knowledge in active pedagogies. In conclusion, we highlight the need to design training and professional development programs that enhance the digital competence of active primary education teachers, with an emphasis on training schemes geared towards robotics and educational programming.